Of Human Bondage Based on a Novel by W. Somerset Maugham - Maugham, William S. (Kino Classics, 2013)
Philip Carey (Leslie Howard) is a sensitive but unsuccessful artist living in Paris who abandons his fanciful ambitions and enrolls in a London medical school. Despite a slight physical deformity he overcomes his awkwardness and falls in love with a low-class, money-hungry waitress, Mildred Rogers (Bette Davis, in her Oscar nominated performance). Philip is obsessed with the callous woman, but when he discovers Mildred has been dating other men, he finally realizes the relationship is over and finds a new love. Although Mildred runs off with another medical student, Philip takes her back when she returns with news that she is pregnant. Mildred continues to treat him badly, and Philip's devotion to her threatens his career and his chance for future happiness. [www.amazon.com]